Factors influencing green warehouse practices in Malaysian warehouse industry: an empirical analysis / Siti Norida Wahab, Nazura Mohamed Sayuti and Azimah Daud - Wahab, Siti Norida; Mohamed Sayuti, Nazura; Daud, Azimah (Universiti Teknologi MARA, Shah Alam, 2019)
The purpose of this study is to provide an understanding of the factors influencing green warehouse practices (GWP) in the Malaysian warehouse industry. Both stakeholder theory (ST) and institutional theory (IT) act as the foundation in developing the theoretical framework. Six factors were identified resulted from preliminary data gathering and an extensive literature review for constructing the model. The sample size consists of 226 respondents with the acceptance rate of 89 per cent. The findings revealed that customer demand, owner support, employee involvement, top management commitment, industry competition, and governmental pressure are positively associated with GWP. Based on the findings, warehouse companies and relevant authorities in Malaysia should focus on the importance of GWP towards becoming more competitive in the global market. The study provides a theoretical gap by proposing a valuable implication to scholars and practitioners in promoting sustainable industrial development which aligns with the government national agenda.